2015
DOI: 10.1080/01694243.2015.1115616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing for core preparation, luting cement type and root level on adhesion of fiber posts to intraradicular dentin

Abstract: This study assessed the effect of timing of core preparation and luting cement on adhesion of fiber reinforced composite (FRC) posts on different levels of intraradicular dentin when cemented with either conventional dual-polymerized or self-adhesive resin cement.Single-rooted human teeth (N=80) were endodontically treated and randomly divided into 2 groups (n=40) according to resin cement: a) Conventional dual resin cement (Variolink II, V) or b) Self-adhesive resin cement (RelyX U200, R). They were further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
1
1
Order By: Relevance
“…The results of this study were comparable with those of Perez et al, where a 7 to 8 MPa bond strength was reported [30]. On the other hand, the results were higher than those of Sukuroglu et al [31] where adhesion results ranged between 3.8 and 5.6 MPa in the coronal region of the root. Both of these studies [30,31] reported push-out bond strength results whereas in this study tensile bond strength was measured.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this study were comparable with those of Perez et al, where a 7 to 8 MPa bond strength was reported [30]. On the other hand, the results were higher than those of Sukuroglu et al [31] where adhesion results ranged between 3.8 and 5.6 MPa in the coronal region of the root. Both of these studies [30,31] reported push-out bond strength results whereas in this study tensile bond strength was measured.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the results were higher than those of Sukuroglu et al [31] where adhesion results ranged between 3.8 and 5.6 MPa in the coronal region of the root. Both of these studies [30,31] reported push-out bond strength results whereas in this study tensile bond strength was measured. Nevertheless, the use of dual polymerized cement in this study resulted in higher bond strength values with self-adhesive cements [30] in the coronal parts of the intraradicular dentin.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation